SG-APSIC1178: Factors influencing COVID-19 prevention practices among healthcare personnel in Rajavithi Hospital - Kampong Kamnon (Cambridge University Press, 2023)
Objectives: To determine the factors influencing COVID-19 prevention practices among healthcare personnel. Methods: The sample consisted of healthcare personnel working in the emergency department, inpatient wards, and the outpatient department in 250 Rajavithi hospitals selected using a purposive sampling method. Data were collected using questionnaires that were validated by 5 experts and had a content validity index of 0.83. The reliability of the questionnaires was 0.91. Data were analyzed using descriptive statistics and multiple regression. Results: Study participants had good attitudes toward behaviors, subjective norms, perceived behavioral control, and intention to prevent COVID-19. In addition, perceived behavioral control was the only factor that statistically predicted intention to perform COVID-19 infection prevention and may explain 25.6% of the variability of intention (P < .001). Conclusions: Based on the results of this study, relevant authorities, including wards and infection control units, should support perceived behavioral control among registered nurses to encourage COVID-19 prevention practices.